OPTIMIZATION OF THE AUTHORITY OF THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) IN MANAGING REGIONAL ASSETS IN MEDAN CITY - Sintara, Dani (NOMOI Law Review, 2024)
The Regional Financial and Asset Management Agency is part of the regional apparatus organization that handles matters supporting regional government. As an agency that has a function to support government affairs, the BPKAD in Medan City has several authorities related to the management of regional finances and assets. The large number of regional assets in Medan City that have not been optimally managed is a separate problem related to the management of regional finances and assets. This study uses normative legal research with the approach used through the statute approach. This means that this study aims to see whether the authority of the BPKAD, especially in Medan City, has been implemented optimally or not. In the end, it is seen that the position of the BPKAD in Medan City as an agency is included in the agency that constitutionally has a clear legal basis. However, related to its authority, it is seen that the BPKAD in Medan City has not been able to optimally implement its authority in managing regional finances and assets in Medan City. So there needs to be improvement related to the performance of the BPKAD.